Safety, Tolerability, and Pharmacokinetic Evaluation of Single and Multiple Doses of the Dipeptidyl Peptidase 1 Inhibitor Brensocatib in Healthy Japanese and White Adults. Issue 7 (11th April 2022) - Usansky, Helen; Yoon, Esther; Teper, Ariel; Zou, Jun; Fernandez, Carlos
Abstract: Brensocatib, an investigational first‐in‐class, small‐molecule, orally bioavailable, selective, and reversible dipeptidyl peptidase 1 inhibitor that blocks activation of neutrophil serine proteases, is currently under clinical development for the treatment of bronchiectasis and other chronic inflammatory diseases. In a 2‐part phase 1 study, the safety, tolerability, and pharmacokinetics of brensocatib were evaluated in healthy Japanese and White adults. In part A, participants received single and multiple once‐daily doses of brensocatib (10, 25, or 40 mg) or placebo after an overnight fast. In part B, participants received a single oral dose of brensocatib 40 mg on days 1 and 8, with or without food in a crossover fashion. Following a single dose and at steady state, brensocatib exposure was dose dependent, with low to moderate interindividual variability; systemic exposure between Japanese and White participants was similar. Elimination half‐life of brensocatib ranged from 22 to 28 hours, resulting in ≈2‐fold accumulation in maximum plasma concentration and area under the plasma concentration–time curve at steady state. In both ethnic groups, the presence of food slightly delayed brensocatib absorption with time to maximum plasma concentration increased by 0.7 to 1.7 hours, but it had no significant effect on brensocatib exposure (maximum plasma concentration and area under the plasma concentration–time curve). Brensocatib was well tolerated in Japanese and White participants. The most frequently reported treatment‐emergent adverse events were headache and skin exfoliation. No clinically significant vital signs, laboratory abnormalities, or evidence of renal toxicity were observed. The results from this study demonstrate that brensocatib can be administered with or without food and that dose adjustment is unnecessary for Japanese patients when receiving brensocatib treatment.